Common Errors Found in the Diverse Kinds of Paragraphs Composed by First Year EFL University Students - Ida Ayu Mela Tustiawati (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2023)
The present study aims at showing the major types of errors that students make in their written products and their perspectives on the cause of errors that they make. In this research, 180 students’ paragraphs were analysed for the purpose of error analysis and a questionnaire was distributed to the students to find out their perspectives on the cause of errors that they made. The errors found in the students’ written products were first categorised into several major categories, then further classified into four general categories: morphological, lexical, syntactical, and mechanical. The findings show that there were 12 major errors that the students made in their writing. Seven of them fall under the category of morphological, two under lexical, one under syntactical and another two under mechanical. The majority of students are aware that they make errors in their writing but find it hard to allocate them. As a result, they may not be able to correct or avoid the errors. Thus, incorporating error analysis in teaching and learning is a necessary practice for students to minimise the production of errors in their writing. Furthermore, lack of understanding of grammatical functions and limited knowledge of vocabulary are considered the major causes of errors based on the perspectives of the students. Through the classification system provided by the error analysis procedure, teachers are able to address this issue by incorporating smaller groupings of errors into the curriculum and teaching program